Frequency-selective-surface based sandwich structure for both effective loadbearing and customizable microwave absorption - Wang, Changxian (2022)
Multifunctional composite structure with unique mechanical and physical characteristics is essential for the lightweight design of engineering structures. Here, we develop a multifunctional sandwich structure for both effective loadbearing and customizable microwave absorption by employing glass fiber reinforced plastic, polyvinyl chloride foam, carbon fiber reinforced plastic, and frequency selective surfaces. The resultant sandwich structures are endowed with effective specific flexure stiffness (up to 130 N/mm), benefiting from the efficiency in material distribution configuration. Moreover, the proposed structures also show highly customizable microwave absorbing capacity in both bandwidth (from 2 GHz to 18 GHz) and band depth (from −10 dB to −15 dB), due to the flexible design ability of multiple interfaces, electromagnetic loss artificial film. The optimized structures highlight a tradeoff among microwave absorption, flexure stiffness, and surface density and thus are promising a smart stage on which high-performance customizable properties can be envisaged.